The Relationship Of Knowledge About Healthy And Clean Living Behavior With Attitude To Preventing The Transmission Of Covid 19 At Hujjaturrahmah Islamic Boarding School Tanjung Pura Langkat District In 2021 - Arnof Yerni; Putri Ramadani; Nurainun; Intan Agustin (Science Midwifery, 2021)
Clean and healthy behavior (PBHS). washing hands with soap and wearing masks. Hand washing with soap (CTPS) is one of the output indicators of the STBM national strategy (Community-Based Total Sanitation), namely every household and public service facilities in a community (such as schools, offices, restaurants, health centers, markets, terminals, cottages). Islamic boarding schools) there are hand washing facilities (water, soap, hand washing facilities), so that everyone washes their hands properly. This study aims to determine the relationship between knowledge about PHBS and prevention of covid 19 transmission in Hujjaturrahmah Tanjung Pura Islamic Boarding School, Langkat Regency in 2021. This study using a descriptive correlation study, which is the type of research used to determine the relationship between a variable and other variables (Notoadmodjo, 2017). The population in this study was 40 people from the Hujjaturrahmah Islamic boarding school students and the sampling technique was total sampling. The variables identified were PHBS knowledge with covid 19 prevention. The results of the univariate analysis of knowledge obtained were 28 respondents (70%) good and not good enough as many as 12 respondents (30%), while regarding the prevention of covid 19 transmission, it was found that most of the covid-19 prevention was carried out well as many as 24 respondents (60%) ) and not good 16 respondents (40%).While the bivariate analysis using the chi square test obtained a p value of 0.003 (<0.05) so that it can be seen that there is a significant relationship betweenrespondent's knowledge about PHBSwith the prevention of COVID-19 at the Hujjaturrahmah Islamic Boarding School Tanjung Pura, Langkat Regency in 2021.